DINAMIKA STIGMA SOSIAL ASKES HUNIAN KOS BAGI PENDATANG ASAL NTT DI BALI - Maria Diana Murni Mensi; I Nyoman Subanda (CV. Lafadz Jaya, 2026)
The increasing migration of people from East Nusa Tenggara (NTT) to Bali has generated various social dynamics, including the emergence of social stigma that affects migrants' access to boarding houses (kos). This study aims to analyze the dynamics of social stigma experienced by NTT migrants in obtaining boarding house accommodation in Denpasar, Bali. A descriptive qualitative approach was employed using in-depth interviews, observations, and documentation. The study involved nine purposively selected informants consisting of three boarding house owners, three local Balinese residents, and three migrants from NTT. Data were analyzed using the Miles and Huberman interactive analysis model and interpreted through Erving Goffman's stigma theory alongside the stigma process proposed by Link and Phelan, encompassing labeling, stereotyping, separation, and discrimination. The findings reveal that social stigma toward NTT migrants is primarily shaped by the generalization of the behavior of a small number of individuals, reinforced by media exposure, personal experiences, and narratives circulating within the community. These perceptions subsequently develop into stereotypes that influence boarding house owners' decisions, leading to more selective rental practices and, in some cases, discriminatory treatment based solely on regional origin. Consequently, many NTT migrants experience difficulties in securing accommodation, psychological pressure, social exclusion, and the need to continuously demonstrate positive behavior to challenge existing stereotypes. Nevertheless, the study also finds that direct interpersonal interaction, consistent adherence to social norms, and effective communication contribute significantly to reducing prejudice and fostering greater acceptance. This study concludes that social stigma toward NTT migrants extends beyond individual prejudice and has become a structural barrier affecting equal access to housing. Therefore, strengthening intercultural communication, promoting objective media representation, and implementing inclusive housing policies are essential to reducing discrimination and encouraging social cohesion between local communities and migrant populations.